Surface coated cutting tools
By introducing NaCl-type face-centered cubic structure grains into the TiAlCN layer of the cladding tool, and designing the repeated interval of Al content in the grains, the problem of scaling in high-speed intermittent cutting is solved, and the tool's scaling resistance and wear resistance are improved.
Patent Information
- Application Number
- CN202180027449.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-03
- Filing Date
- 2021-02-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-02-03
AI Technical Summary
Existing cladding tools are prone to abnormal losses such as cracking during high-speed intermittent cutting, which cannot meet the needs of high-speed and efficient.
The TiAlCN layer with a NaCl-type face-centered cubic structure is used as the hard cladding layer. By the presence of Al in the prescribed area ratio in the grain, the movement of dislocation is suppressed, and the hardness and wear resistance are improved.
It significantly improves the scaffolding and wear resistance of the cladding tool, extends the service life of the tool, and maintains excellent cutting performance during long-term use.
Smart Images

Figure CN115397589B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a surface-coated cutting tool (hereinafter sometimes referred to as a coated tool), which has excellent chipping resistance and wear resistance due to the hard coating layer, and exhibits excellent cutting performance even in high-speed intermittent cutting of alloy steel, cast iron, etc., and can also exhibit excellent cutting performance during long-term use.
[0002] This application claims priority based on patent application No. 2020-016659 filed in Japan on February 3, 2020, and the contents are incorporated herein by reference. Background Art
[0003] Conventionally, there are known coated tools in which a Ti—Al composite carbonitride layer is formed as a hard coating layer by vapor deposition on the surface of a tool substrate such as tungsten carbide (hereinafter referred to as WC)-based cemented carbide, and these tools exhibit excellent wear resistance.
[0004] However, the aforementioned conventional coated tools having a Ti—Al composite carbonitride layer have relatively excellent wear resistance, but are prone to abnormal wear such as chipping when used under severe cutting conditions such as high-speed intermittent cutting. Therefore, various schemes have been proposed to improve the durability of the hard coating layer.
[0005] For example, Patent Document 1 describes a coated tool which is coated with a hard material and is characterized in that it has a plurality of layers formed by CVD. 1-x Al x N layer and / or Ti 1-x Al x C layer and / or Ti 1-x Al x Al is arranged on the CN layer (where x is 0.65 to 0.95) 2 O 3 layer as the outer layer.
[0006] Furthermore, for example, Patent Document 2 describes a coated tool comprising a tool substrate and one or more hard coating layers formed on the surface thereof, wherein at least one of the hard coating layers is a layer comprising hard particles, and the hard particles comprise a multilayer structure formed by alternatingly stacking a first unit layer and a second unit layer, wherein the first unit layer comprises a first compound, the first compound being composed of one or more elements selected from elements of Groups 4 to 6 of the periodic table and Al and one or more elements selected from B, C, N and O, and the second unit layer comprising a second compound, the second compound being composed of one or more elements selected from elements of Groups 4 to 6 of the periodic table and Al and one or more elements selected from B, C, N and O.
[0007] In addition, for example, Patent Document 3 describes a coated tool including a coating layer composed of one layer or two or more layers, at least one of which is composed of Ti alternately stacked layers. 1-x Al x The first unit layer is composed of N and Ti 1- y Al y The second unit layer is composed of a multi-layered coating layer of N, and the first unit layer has an fcc type crystal structure, the Ti 1-x Al x x in N satisfies 0<x<0.65, the second unit layer has an hcp type crystal structure, and the Ti 1- y Al y y in N satisfies 0.65≤y<1, and the elastic recovery rate of the coating layer in the thickness direction is 50% or more.
[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-516722 (A)
[0009] Patent Document 2: Japanese Patent Application Publication No. 2014-129562 (A)
[0010] Patent Document 3: Japanese Patent No. 6238131 (A)
[0011] In recent years, there has been a strong demand for labor saving and energy saving in cutting processing. As a result, cutting processing has tended to be further accelerated and efficient. The coated tools are further required to have resistance to abnormal damage such as chipping resistance, defect resistance, and peeling resistance, and are required to have excellent wear resistance during long-term use. However, the coated tools described in the aforementioned publications cannot fully meet these requirements. Summary of the invention
[0012] Therefore, the present invention has been made in view of such circumstances, and an object of the present invention is to provide a coated tool that exhibits excellent chipping resistance and wear resistance during long-term use even when used for high-speed intermittent cutting of alloy steel, cast iron, etc.
[0013] The present inventors have conducted intensive studies to achieve chipping resistance and wear resistance of a coated tool including a composite carbonitride layer of Ti and Al (hereinafter, sometimes referred to as a TiAlCN layer) as a hard coating layer.
[0014] As a result, new findings described below were obtained.
[0015] As a grain having a NaCl-type face-centered cubic structure in the TiAlCN layer, if there are two grains with different composition changes in which the content ratio of Al in the total amount of Ti and Al increases and decreases at a predetermined area ratio in the grain, the movement of dislocations is suppressed, the hardness is increased, and the wear resistance is improved. In addition, the toughness is improved, thereby preventing the expansion of cracks caused by the shear force acting on the surface where wear progresses during cutting, and the increase in lattice defects caused by the increase in strain of the TiAlCN layer is alleviated, thereby suppressing the formation of a path for crack expansion. As a result, the chipping resistance of the surface-coated cutting tool is further improved.
[0016] Aspects of the present invention (hereinafter referred to as "surface-coated cutting tool of the present invention") are as follows based on the above findings.
[0017] (1) A surface-coated cutting tool comprising a tool base body and a hard coating layer including a composite carbonitride layer of Ti and Al on the surface of the tool base body, wherein:
[0018] (a) in the Ti and Al composite carbonitride layer, the proportion of the grains of Ti and Al composite carbonitride having a NaCl-type face-centered cubic structure is 80% by area or more,
[0019] (b) Regarding the composite carbonitride layer of Ti and Al, its composition is as follows: (Ti 1-x Al x )(C y N 1-y ) is expressed as, the average x of the content ratio x of Al in the total amount of Al and Ti avg Satisfy 0.60≤x avg ≤0.90, average y of the C content ratio y in the total amount of C and N avg Satisfy 0.000≤y avg ≤0.050(where x, y, x avg ,y avg is the atomic ratio),
[0020] (c) the NaCl-type face-centered cubic grains include grains in which x repeatedly increases and decreases in a direction perpendicular to the surface of the tool substrate,
[0021] (d) as the repeatedly increasing and decreasing grains, 10 to 40 area % of the first interval d having the repeatedly increasing and decreasing average interval of 40 to 160 nm is included avgl The grain G of the region l ,
[0022] (e) as the repeatedly increasing and decreasing grains, 60% by area or more of the grains have the second spacing d having the repeatedly increasing and decreasing average spacing of 1 to 7 nm. avgs The grain G of the region s .
[0023] (2) The surface-coated cutting tool according to (1) above, characterized in that:
[0024] As the repeatedly increased and decreased grains, 10 to 30% by area of the grains simultaneously include the first interval d avgl and the second interval d avgs The grain G of each region ls .
[0025] (3) The surface-coated cutting tool according to (1) or (2), characterized in that:
[0026] The average particle width w of the NaCl-type face-centered cubic structure grains is 0.10-2.00 μm, and the average aspect ratio A is 2.0-10.0.
[0027] (4) The surface-coated cutting tool according to any one of (1) to (3), characterized in that:
[0028] In the grains that repeatedly increase and decrease, the adjacent maximum values x in the repeated increase and decrease of x max With the minimum value x min The average value of the difference Δx in the first interval d avgl In the region of 0.05 to 0.20, in the region of the second interval d avgs In the region of 0.03 to 0.10.
[0029] The surface-coated cutting tool of the present invention exhibits excellent chipping resistance and wear resistance during long-term use even when used for high-speed intermittent cutting of alloy steel, cast iron, and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of a high-angle annular dark field image of a grain of a NaCl-type face-centered cubic structure having repeated regions of increase and decrease of the Al content ratio x.
[0031] Figure 2 It is a schematic diagram showing the measurement sites by line analysis based on energy dispersive X-ray spectroscopy using a transmission electron microscope.
[0032] Figure 3This is a schematic diagram showing the relationship between the position of the observation direction in line analysis based on energy dispersive X-ray spectroscopy using a transmission electron microscope and the repetition of increase and decrease of the Al content ratio x. DETAILED DESCRIPTION
[0033] The surface coated cutting tool of the present invention is described in detail below. In addition, when a numerical range is expressed by "A to B" in this specification and claims, the range includes the numerical values of the upper limit (B) and the lower limit (A). Moreover, the units of the upper limit (B) and the lower limit (A) are the same.
[0034] Average thickness of TiAlCN layer:
[0035] The TiAlCN layer of the surface-coated cutting tool of the present invention constitutes a hard coating layer. That is, the hard coating layer includes a TiAlCN layer. The average layer thickness of the TiAlCN layer is preferably 1.0 to 20.0 μm. When the average layer thickness is less than 1.0 μm, the wear resistance in long-term use cannot be fully ensured due to the thin layer thickness. On the other hand, if the average layer thickness exceeds 20.0 μm, the grains of the TiAlCN layer are easily coarsened and chipping occurs easily. The average layer thickness is more preferably 3.0 to 15.0 μm.
[0036] Here, the average layer thickness of the TiAlCN layer can be obtained as follows: using a focused ion beam device (FIB: Focused Ion Beam system), a cross section polisher (CP: Cross section Polisher), etc., the TiAlCN layer is cut in a longitudinal section (a surface perpendicular to the surface of the tool substrate) at an arbitrary position to prepare an observation sample, and a scanning electron microscope (SEM: Scanning Electron Microscope) or a transmission electron microscope (TEM: Transmission Electron Microscope), a scanning transmission electron microscope (STEM: Scanning Transmission Electron Microscope) or an energy dispersive X-ray analysis (EDX: Energy Dispersive X-ray spectrometry) device with a SEM or TEM is used to observe multiple parts (for example, 5 parts) of the longitudinal section and average them.
[0037] The area ratio of the grains constituting the TiAlCN layer with a NaCl-type face-centered cubic structure is:
[0038] The area ratio of the TiAlCN grains constituting the TiAlCN layer to a NaCl-type face-centered cubic structure is preferably 80 area % or more. The reason is that if it is 80 area % or more, the purpose of the present invention can be achieved more reliably. In addition, all of the grains can be a NaCl-type face-centered cubic structure (can be 100 area %).
[0039] The area ratio of the crystal grains having the NaCl type face-centered cubic structure is determined by using the result of the determination of the grain boundary 1 described later.
[0040] The area ratio refers to the area ratio in the longitudinal section of the TiAlCN layer.
[0041] Average composition of TiAlCN layer:
[0042] The composition of the TiAlCN layer in the surface-coated cutting tool of the present invention is as follows: (Ti 1-x Al x )(C y N 1-y ), preferably the average content ratio x of Al in the total amount of Ti and Al (hereinafter referred to as "the average Al content ratio") x avg Satisfy 0.60≤x avg ≤0.90, the average of the C content ratio y in the total amount of C and N (hereinafter referred to as "the average C content ratio") y avg Satisfy 0.000≤y avg ≤0.050(where x avg ,y avg are all atomic ratios).
[0043] In addition, (Ti 1-x Al x ) and (C y N 1-y ) is not particularly limited, but when (Ti 1-x Al x ) is set to 1, (C y N 1-y ) is preferably set to 0.8 to 1.2.
[0044] The reason for this is as follows.
[0045] If the average Al content x avg If the value is less than 0.60, the hardness of the TiAlCN layer is poor, so the wear resistance is insufficient in the case of high-speed intermittent cutting of alloy steel, cast iron, etc. On the other hand, if it exceeds 0.90, hexagonal crystal grains are precipitated, and the wear resistance is reduced. Therefore, it is preferred that 0.60≤x avg ≤0.90, more preferably 0.70≤x avg≤0.90.
[0046] And, as the average C content ratio y avg The preferred range is 0.000≤y avg The reason why y is ≤0.050 is that the hardness can be increased while maintaining the chipping resistance within the above range. avg ≤0.050, more preferably 0.010≤y avg ≤0.050.
[0047] The average Al content ratio of the TiAlCN layer avg It is obtained by the following method: using Auger electron spectroscopy (AES), in a sample whose cross section has been ground, an electron beam is irradiated from the longitudinal section side, and at least 5 lines are analyzed along the entire length in the film thickness direction (the direction perpendicular to the surface of the tool substrate), and the obtained Auger electron analysis results are averaged.
[0048] And, the average y of C content ratio avg It is obtained by secondary ion mass spectrometry (SIMS). That is, in a sample whose surface has been polished, an ion beam is irradiated from the surface side of the TiAlCN layer in a range of 70μm×70μm, and surface analysis based on the ion beam and etching based on the sputtering ion beam are repeated alternately to measure the composition in the depth direction. First, a depth measurement of at least 0.5μm is performed at intervals of less than 0.1μm from a position more than 0.5μm into the depth direction of the TiAlCN layer, and the average value of the obtained data is obtained. Moreover, it is repeated at least at 5 locations on the surface of the sample, and the calculated results are averaged to obtain the average C content ratio y avg Find out.
[0049] Repeated increase and decrease of the Al content ratio x of the TiAlCN layer:
[0050] In the longitudinal section of the TiAlCN layer, it is preferred that the average interval of repeated increase and decrease of the content ratio x of Al in the total amount of Ti and Al in the layer thickness direction 3 be 40 to 160 nm. avgl The grain G of the region l and a second interval d having the interval being 1 to 7 nm avgs The crystal grains Gs in the region of 10 to 40 area % and 60 area % or more exist respectively. In addition, the layer thickness direction 3 refers to the thickness direction of the TiAlCN layer, and the tolerance in measurement, that is, the deviation of about 10 degrees is allowed in this direction.
[0051] About Crystal G l , is defined as having a first interval d avgl area, but this provision refers to the grain G l If there is an average interval of repeated increase and decrease of x, the first interval d avgl In the region, there may be a second interval d where the average interval of repeated increases and decreases of x is avgs Similarly, regarding the grain G s , is specified to have a second interval d avgs However, this provision means that if there is an average interval of repeated increases and decreases of x, the second interval d avgs In the region, there may be a first interval d where the average interval of repeated increase and decrease of x is avgl area or other interval areas.
[0052] Here, the repetition of increase and decrease of the Al content ratio x means that, in the layer thickness direction 3, when the line analysis described later is performed, the increase and decrease of the Al content ratio x are repeated adjacently. And, in this adjacent repetition, the interval between adjacent maximum values or the interval between adjacent minimum values is called the interval of increase and decrease repetition, and the average value of this interval for each analysis line 2 of the line analysis is divided into the above-mentioned first interval and second interval.
[0053] If the first interval d avgl The repeated increase and decrease of the interval between grains G l If it is less than 10 area %, it is not possible to fully achieve the improvement of hardness and the suppression of crack propagation by suppressing the movement of dislocations in the surface where wear progresses during cutting. On the other hand, if it exceeds 40 area %, the lattice defects increase as the strain of the TiAlCN layer increases, so the hardness decreases, and many crack propagation paths are formed, resulting in reduced chipping resistance.
[0054] And, if there is a second interval d avgs The repeated increase and decrease of the interval between grains G s If the content is less than 60 area %, the hardness cannot be sufficiently improved by suppressing the movement of dislocations, and the effect of suppressing crack growth becomes small, resulting in reduced chipping resistance.
[0055] Furthermore, in the longitudinal section of the TiAlCN layer, it is more preferable that the first spacer d avgl and the second interval d avgs The NaCl-type face-centered cubic grain G ls The area % of the crystal grains G ls The presence of 10 to 30 area % can more reliably suppress the propagation of cracks.
[0056] The adjacent maximum value x of the Al content ratio x max With the minimum value x min The average value of the difference Δx:
[0057] The adjacent maximum value x of the Al content ratio x max With the minimum value x min The average value Δx of the difference is preferably in the first interval d avgl In the region of 0.05 to 0.20, in ... avgs The reason is that if the first interval d avgl is less than 0.05 in the region with the second interval d avgs If the area with the first interval d is less than 0.03, the effect of suppressing crack propagation during cutting becomes small and the chipping resistance decreases. On the other hand, if the area with the first interval d avgl In the region where the second interval d avgs When the ratio exceeds 0.10 in the region of , the lattice strain of the grains becomes too large, lattice defects increase, and wear resistance and chipping resistance decrease.
[0058] exist Figure 1 A schematic diagram of a high-angle annular dark field image of a grain having repeated regions of increase and decrease of the Al content ratio x is shown in FIG. Figure 1 In the figure, three grains are shown, and the central grain is G s , the two neighboring grains are G ls Since this is a schematic diagram, the size of each crystal grain and the interval of repeated changes in the increase and decrease of the Al content ratio x that can be read from the figure do not represent the exact size (ratio).
[0059] Here, a method for measuring repeated changes in increase and decrease of the Al content ratio x of the TiAlCN layer will be described.
[0060] First, the grain boundaries of the grains constituting the TiAlCN layer are obtained and the grains are determined in the following manner. That is, a crystal orientation analysis device attached to a transmission electron microscope (TEM) is used to irradiate the surface of the surface-polished surface (longitudinal section) perpendicular to the surface of the tool substrate with an electron beam inclined 0.5 to 1.0 degrees relative to the normal direction of the surface-polished surface, while scanning the electron beam with an arbitrary beam diameter and interval, continuously reading the electron diffraction pattern, and analyzing the crystal orientation of each measurement point. The grain boundaries are determined for an observation field with a width of 50 μm in the direction parallel to the surface of the tool substrate and a layer thickness (average layer thickness) dimension in the longitudinal direction.
[0061] In addition, the acquisition conditions of the electron beam diffraction pattern used in this measurement are an acceleration voltage of 200kV, a camera length of 20cm, a beam size of 2.4nm, and a measurement step of 5.0nm. At this time, the measured crystal orientation is obtained by discretely investigating the measurement surface, and the region up to the middle between adjacent measurement points is represented by the measurement result, so as to obtain the orientation distribution of the entire measurement surface. In addition, as the region represented by these measurement points (hereinafter, sometimes referred to as a pixel), a regular hexagonal region can be exemplified. In the case where there is an angle difference of more than 5 degrees of crystal orientation between adjacent pixels in the pixel, or in the case where only one side of the adjacent pixels shows a NaCl-type face-centered cubic structure, the edge of the region contacted by these pixels is set to a grain boundary 1. And, the portion surrounded by the edge set to the grain boundary 1 is defined as a grain. However, a single pixel such as a single pixel having an orientation difference of more than 5 degrees with all adjacent pixels, or a measurement point having a NaCl-type face-centered cubic structure that does not exist adjacent to the pixel is not considered a grain, and a pixel connected to more than two pixels is considered a grain. In this way, the grain boundaries are determined and the grains are identified.
[0062] Next, the method for determining the average interval of the repeated increase and decrease of the Al content ratio x of the TiAlCN layer is described. The definition includes an observation field of at least 10 grains determined by the above steps, and each grain is subjected to a line analysis along the layer thickness direction 3 by using Energy Dispersive X-ray Spectrometry (EDS) using TEM (the measurement interval is less than 0.5nm). That is, Figure 2 As shown, when the grain is divided into three equal parts along the layer thickness direction 3, the upper part R of the grain U , Central R M , lower R L In each range, five line analyses are performed along the layer thickness direction 3. This line analysis is performed on all grains in the observation field. U , R M , R L The intervals of the five lines analyzed in each range are set to the intervals that divide the maximum length in the direction horizontal to the surface of the tool substrate into six equal parts. The length of the analysis line 2 for each grain is set to the length at which the number of intervals of repeated increase and decrease of the Al content ratio x is 2 or more. However, when the average value of the intervals becomes 7nm or less, the length of the analysis line 2 is set to 80nm, and there are U , R M , R LWhen the length of each layer thickness direction is less than 80 nm, the entire length of the layer thickness direction 3 is analyzed within the range less than 80 nm. Then, the average value (average interval) of the repeated increase and decrease of the Al content ratio x in each analysis line 2 is obtained.
[0063] At this time, when a crystal grain includes two or more analysis lines 2 with an average interval of 40 to 160 nm, the crystal grain is defined as having the first interval d avgl Furthermore, when a crystal grain includes two or more analysis lines 2 with an average interval of 1 to 7 nm, the crystal grain is defined as having the second interval d avgs Furthermore, the number of grains having the first interval d in the observation field is calculated. avgl and the second interval d avgs The area ratio of the grains.
[0064] Here, of course, with the first interval d avgl The grains have the second spacing d avgs There are grains that are counted repeatedly when calculating the area ratio.
[0065] The adjacent maximum value x of the Al content ratio x max With the minimum value x min The method of obtaining the average value Δx of the difference between avgl The area of Δx is defined as Δx l , will have a second interval d avgs The area of Δx is defined as Δx s .
[0066] Line analysis was performed as described above, with the first interval d avgl For each analysis line 2 of Al content ratio x, find the adjacent maximum value x in the repeated increase and decrease max With the minimum value x min Then, the average value is calculated relative to the first interval d. avgl All analysis lines 2 are averaged and the resulting value is calculated as Δx l About Δx s , similarly, according to the second interval d avgs For each analysis line 2 of Al content ratio x, find the adjacent maximum value x in the repeated increase and decrease max With the minimum value x min The average value of the difference between the average value and the second interval d avgs All analysis lines 2 are averaged and the resulting value is calculated as Δx s .
[0067] Here, the average interval of the repetition of the increase and decrease of the Al content ratio x in each analysis line 2 is obtained as follows. The relationship between the position in the observation direction and the repetition of the increase and decrease of the Al content ratio x is plotted as a graph, and the average interval d is obtained. avgl and avgs That is, the repeated increase and decrease of the Al content ratio x is measured, and a straight line m (m) crossing the curve representing the repeated increase and decrease is drawn (reference Figure 3 ). With respect to the straight line m, the area of the region surrounded by the curve is equal on the upper side and the lower side of the straight line. And, the maximum value or the minimum value is obtained for each region where the straight line m crosses the curve representing the repeated change of the Al content ratio x. In addition, of course, when the graph is formed, the known measurement noise removal is performed.
[0068] In addition, Figure 1 In FIG. 1 , the black area indicates the area above the straight line m, and the white area indicates the area below the straight line m.
[0069] Furthermore, the first spacer d is included in the same crystal grain. avgl and the second interval d avgs The NaCl-type face-centered cubic grain G ls , for the upper R of each grain U , Central R M , lower R L When five lines are analyzed in each range, the average value of the repeated intervals D of the increase and decrease of the Al content ratio x in each analysis line 2 is obtained. When two or more analysis lines 2 with average intervals of 40 to 160 nm and 1 to 7 nm exist in the same grain at the same time, the grain is defined as grain G. ls .
[0070] Average particle width W and average aspect ratio A of the TiAlCN layer:
[0071] In the surface-coated cutting tool of the present invention, the TiAlCN layer has a columnar crystal structure, and the average particle width W in the longitudinal section of the crystal grains in the structure is preferably 0.10 to 2.00 μm, and the average aspect ratio A is preferably 2.0 to 10.0. The reason is that if the average particle width W is less than 0.10 μm, the increase in grain boundaries 1 may cause a decrease in plastic deformation resistance and oxidation resistance, which may easily lead to abnormal damage. On the other hand, if the average particle width W is greater than 2.00 μm, the presence of coarsely grown particles may easily lead to a decrease in toughness. Furthermore, if the granular crystal has an average aspect ratio A of less than 2.0, the interface is likely to become a starting point of damage and sometimes a cause of chipping when cutting, relative to the shear stress generated on the surface of the hard coating layer. Moreover, if the average aspect ratio A exceeds 10.0, slight chipping occurs on the blade during cutting. When the adjacent columnar crystal structure is defective, the resistance to the shear stress generated on the surface of the hard coating layer is likely to decrease, and the damage is rapidly extended due to the fracture of the columnar crystal structure, and sometimes large chipping occurs. Therefore, the average particle width W of the crystal grains is more preferably 0.10 to 2.00 μm, and the average aspect ratio A is more preferably 2.0 to 10.0.
[0072] Next, the calculation method of the average grain width W and average aspect ratio A of the grains and the area ratio of the grains having the NaCl type face-centered cubic structure with the columnar crystal structure is described. First, as described above, the grain boundary 1 is determined to identify the grains. Next, image processing is performed to obtain the maximum length H of a grain i in the direction perpendicular to the surface of the tool substrate. i , the maximum length in the direction horizontal to the surface of the tool substrate, i.e. the particle width W i and area S i The aspect ratio A of grain i i Calculated as A i =H i / W i Thus, the grain width W of at least 20 or more (i=1 to 20 or more) grains in the observation field is calculated by using Formula 1. 1 ~W n (n≥20) are area-weighted averaged to obtain the average grain width W of the grains. And, the aspect ratio A of the grains is calculated in the same way. 1 ~A n (n≥20), and the average aspect ratio A of the grains is obtained by performing area-weighted averaging using Formula 2.
[0073] [Formula 1]
[0074]
[0075] [Formula 2]
[0076]
[0077] Other layers:
[0078] As a hard coating layer, the hard coating layer including the TiAlCN layer of the surface-coated cutting tool of the present invention has sufficient chipping resistance and wear resistance in high-speed intermittent cutting processing of alloy steel and cast iron. In addition to the hard coating layer, it also has a lower layer arranged adjacent to the tool substrate (the lower layer is composed of one or more layers of Ti carbide layer, nitride layer, carbonitride layer, carbon oxide layer and carbonitride oxide layer, with a total average layer thickness of 0.1 to 20.0 μm and including a Ti compound (not limited to stoichiometric compound) layer) and / or an upper layer arranged on the TiAlCN layer (the layer including at least an aluminum oxide (not limited to a stoichiometric compound) layer with a total average layer thickness of 1.0 to 25.0 μm is used as the upper layer). When combined with the effects achieved by these layers, it can exert better chipping resistance and wear resistance.
[0079] Here, when the total average thickness of the lower layer is less than 0.1 μm, the effect of the lower layer cannot be fully achieved. On the other hand, if it exceeds 20.0 μm, the grains of the lower layer are easily coarsened and chipping occurs easily. In addition, when the total average thickness of the upper layer including the aluminum oxide layer is less than 1.0 μm, the effect of the upper layer cannot be fully achieved. On the other hand, if it exceeds 25.0 μm, the grains of the upper layer are easily coarsened and chipping occurs easily.
[0080] Tool base:
[0081] As for the tool substrate, any substrate known in the art may be used as long as it does not hinder the achievement of the purpose of the present invention. For example, it is preferably any one of cemented carbide (WC-based cemented carbide, including Co in addition to WC, and carbonitrides of Ti, Ta, Nb, etc.), cermet (materials with TiC, TiN, TiCN, etc. as main components), ceramic (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), cBN sintered body or diamond sintered body.
[0082] Manufacturing method:
[0083] The TiAlCN layer of the surface-coated cutting tool of the present invention can be obtained, for example, by: on the tool substrate or the lower layer (the lower layer is at least one of the carbide layer, nitride layer, carbonitride layer, carbide layer and carbonitride oxide layer of Ti) located on the tool substrate, for example, by injecting a gas group A (gas group A is composed of NH 3 and H2 Composition) and gas group B (gas group B consists of AlCl 3 、TiCl 4 、N 2 , CH 4 , C 2 H 4 , H 2 Two reaction gases of a composition (composition) are supplied through two systems with a specified phase difference, and the two reaction gases are merged in a CVD furnace to obtain a TiAlCN layer.
[0084] The two reaction gas compositions are exemplified as follows: In the gas composition, the sum of the compositions of gas group A and gas group B is set to 100 volume %. The composition of gas group B is composed of system 1 and system 2.
[0085] Gas Group A:
[0086] NH 3 :2.0~5.0%、H 2 : 65~75%
[0087] Gas Group B:
[0088] System 1:
[0089] AlCl 3 :0.65~1.02%、TiCl 4 :0.03~0.43%、N 2 :0.0~10.0%、CH 4 :0.1~3.0%、C 2 H 4 :0.1~3.0%、H 2 : The remainder
[0090] System 2:
[0091] AlCl 3 :0.58~1.03%、TiCl 4 :0.12~0.49%、N 2 :0.0~8.2%、CH 4 :0.1~2.9%、C 2 H 4 :0.1~3.0%、H 2 : The remainder
[0092] Reaction atmosphere pressure: 4.0~5.0kPa
[0093] Reaction atmosphere temperature: 700~850℃
[0094] Gas supply cycle: 2.00~15.00 seconds
[0095] Gas supply time per cycle: 0.15 to 0.25 seconds
[0096] Phase difference between the supply of gas group A and gas group B: 0.10 to 0.20 seconds
[0097] Phase difference between system 1 and system 2: 1.00 to 7.50 seconds
[0098] Example
[0099] Next, examples are described.
[0100] Here, as a specific example of the coated tool of the present invention, the case of being applied to a blade cutting tool using WC-based cemented carbide as the tool substrate is described, but the same is true even when the aforementioned other substrates are used as the tool substrate, and the same is true when applied to drills and end mills.
[0101] As raw material powders, WC powder, TiC powder, TaC powder, NbC powder, CrC powder, and the like, each having an average particle size of 1 to 3 μm, were prepared. 3 C 2 Powder, ZrC powder, TiN powder and Co powder. These raw material powders were blended into the composition shown in Table 1, paraffin was further added and ball-milled in acetone for 24 hours. After the obtained mixed powder was dried under reduced pressure, it was punched into a compact of a specified shape under a pressure of 98 MPa. The compact was vacuum sintered in a vacuum of 5 Pa at a specified temperature in the range of 1370 to 1470°C for 1 hour. After the compact was sintered, WC-based cemented carbide tool substrates A to C with a blade shape of ISO standard SEEN1203AFSN and WC-based cemented carbide tool substrates D to F with a blade shape of ISO standard CNMG120412 were manufactured respectively.
[0102] Next, a TiAlCN layer was formed on the surface of these tool substrates A to F by CVD using a CVD device under the film forming conditions shown in Table 2, thereby obtaining the present invention coated tools 1 to 16 shown in Table 5. Here, as shown in Table 4, in the present invention coated tools 4 to 8, 11, 13, 15, and 16, the lower layer and / or the upper layer were formed under the film forming conditions shown in Table 3.
[0103] Furthermore, for comparison, a TiAlCN layer was formed on the surface of these tool substrates A to F by CVD using a CVD device under the film forming conditions shown in Table 2, thereby obtaining comparative example coated tools 1 to 16 shown in Table 5. Here, as shown in Table 4, in comparative example coated tools 4 to 8, 11, 13, 15, and 16, the lower layer and / or the upper layer were formed under the film forming conditions shown in Table 3.
[0104] [Table 1]
[0105]
[0106] “-”: does not contain.
[0107]
[0108] [Table 3]
[0109]
[0110] [Table 4]
[0111]
[0112] “-”: does not exist [Table 5]
[0113]
[0114] (Note 1) S l , S s They refer to the area ratio of grains satisfying the first average period and the area ratio of grains satisfying the second average period, respectively. (Note 2) S ls It refers to the area ratio of the crystal grains having portions satisfying the first average period and the second average period in the same crystal grain.
[0115] The * in the (Note 3) column indicates that the requirements of claim 1 are not met.
[0116] (Note 4) Regarding comparative coated tools 6, 7, 14, and 15, there are no crystal grains having repeated increases and decreases in the content ratio x of Al.
[0117] (Note 5) Regarding comparative coated tools 8 and 16, there are grains with repeated increases and decreases in the Al content ratio x, but there are no grains with repeated increases and decreases in the Al content ratio x with an average interval of davgl (40 to 160 nm).
[0118] (Note 6) Regarding comparative coated tools 4 and 12, there are grains with repeated increases and decreases in the Al content ratio x, but there are no grains with repeated increases and decreases in the Al content ratio x with an average interval of davgs (1 to 7 nm).
[0119] Next, with respect to the coated tools 1 to 8 of the present invention and the comparative coated tools 1 to 8, the various tool bases A to C (ISO standard SEEN1203AFSN shape) were clamped to the front end of an alloy steel tool with a tool diameter of 80 mm by a fixed fixture, and the wet high-speed front milling and center cutting cutting experiment 1 of the alloy steel shown below was implemented, and the wear width of the back face of the cutting edge was measured. The results of the cutting experiment 1 are shown in Table 6. In addition, with respect to the comparative coated tools 1 to 8, the life was reached before the end of the cutting time due to the occurrence of chipping, so the time until the life was reached is indicated.
[0120] Cutting experiment 1: wet high-speed front milling, center cutting cutting experiment
[0121] Tool diameter: 80mm
[0122] Cutting material: JIS SCM440 block material with a width of 60 mm and a length of 250 mm
[0123] Speed: 1393min -1
[0124] Cutting speed: 350m / min
[0125] Cutting depth: 2.0mm
[0126] Feed: 0.3mm / edge
[0127] Cutting time: 6 minutes
[0128] (Usually the cutting speed is 200m / min)
[0129] [Table 6]
[0130]
[0131] The cutting time (minutes) to reach the life of the comparative coated tool indicates the cutting time (minutes) until the life is reached due to the occurrence of chipping.
[0132] In addition, with respect to the coated tools 9 to 16 of the present invention and the comparative coated tools 9 to 16, the various coated tool bases D to F (ISO standard CNMG120412 shape) were all screwed to the front end of the alloy steel turning tool by a fixing jig, and the dry high-speed intermittent cutting experiment 2 of ductile iron shown below was carried out, and the flank wear width of the cutting edge was measured. The results of the cutting experiment 2 are shown in Table 7. In addition, with respect to the comparative coated tools 9 to 16, the life was reached before the end of the cutting time due to the occurrence of chipping, so the time until the life was reached is shown.
[0133] Cutting experiment 2: wet high-speed interrupted cutting
[0134] Cutting material: JIS FCD700 round bars with 8 longitudinal grooves spaced evenly in the length direction
[0135] Cutting speed: 300m / min
[0136] Cutting depth: 2.0mm
[0137] Feed rate: 0.3mm / rev
[0138] Cutting time: 3 minutes
[0139] (Usually the cutting speed is 200m / min)
[0140] [Table 7]
[0141]
[0142] The cutting time (minutes) to reach the life of the comparative coated tool indicates the cutting time (minutes) until the life is reached due to the occurrence of chipping.
[0143] According to the results shown in Tables 6 and 7, the hard coating layers of the coated tools 1 to 16 of the present invention all have excellent chipping resistance and peeling resistance, so even when used for high-speed intermittent cutting of alloy steel and cast iron, chipping does not occur, and excellent wear resistance is exerted for a long time. In contrast, the comparative coated tools 1 to 16 that do not meet even one of the items specified in the coated tools of the present invention have chipping when used for high-speed intermittent cutting of alloy steel and cast iron, and the service life is reached in a short time.
[0144] Industrial Applicability
[0145] As mentioned above, the coated tool of the present invention can also be used as a coated tool for high-speed intermittent cutting processing other than alloy steel and cast iron, and it can exhibit excellent chipping resistance and wear resistance for a long time. Therefore, it can fully and satisfactorily respond to the high performance of the cutting device, the labor-saving and energy-saving of the cutting processing, and the low cost.
[0146] Description of Reference Numerals
[0147] 1 Grain boundary
[0148] 2 Analysis line based on EDS using TEM
[0149] 3 Layer thickness direction
[0150] D interval
[0151] m straight line m.
Claims
1. A surface-coated cutting tool comprising a tool substrate and a hard coating layer comprising a composite carbonitride layer of Ti and Al on the surface of the tool substrate, wherein the surface-coated cutting tool is characterized in that: (a) in the Ti and Al composite carbonitride layer, the proportion of the grains of Ti and Al composite carbonitride having a NaCl-type face-centered cubic structure is 80% by area or more, (b) Regarding the composite carbonitride layer of Ti and Al, its composition is as follows: (Ti 1-x Al x ) (C y N 1-y ) is expressed as, the average x of the content ratio x of Al in the total amount of Al and Ti avg Satisfy 0.60≤x avg ≤0.90, average y of the C content ratio y in the total amount of C and N avg Satisfy 0.000≤y avg ≤0.050, where x, y, x avg ,y avg is the atomic ratio, (c) the grains of the NaCl-type face-centered cubic structure include grains in which x repeatedly increases and decreases in a direction perpendicular to the surface of the tool substrate, wherein the repeated increase and decrease refer to the adjacent repeated increase and decrease of x, and in the adjacent repetition, the interval between adjacent maximum values or the interval between adjacent minimum values is referred to as the repeated increase and decrease interval, (d) as the repeatedly increasing and decreasing grains, 10 to 40% by area of the first interval d having the repeatedly increasing and decreasing average interval of 40 to 160 nm is included. avgl The grain G of the region l , (e) as the repeatedly increasing and decreasing grains, 60% by area or more of the second spacing d having the repeatedly increasing and decreasing average spacing of 1 to 7 nm is included avgs The grain G of the region s .
2. The surface-coated cutting tool according to claim 1, characterized in that: As the repeatedly increased and decreased grains, 10 to 30% by area of the grains simultaneously include the first interval d avgl and the second interval d avgs The grain G of each region ls .
3. The surface-coated cutting tool according to claim 1 or 2, characterized in that: The average particle width w of the NaCl-type face-centered cubic structure grains is 0.10-2.00 μm, and the average aspect ratio A is 2.0-10.
0.
4. The surface-coated cutting tool according to any one of claims 1 to 3, characterized in that: In the grains that repeatedly increase and decrease, the adjacent maximum values x in the repeated increase and decrease of x max With the minimum value x min The average value of the difference Δx in the first interval d avgl In the region of 0.05 to 0.20, in the region of the second interval d avgs In the region of 0.03 to 0.10.
Citation Information
Patent Citations
Structure of heating toilet seat
JP1987038131A
Objects covered with hard materials
JP2011516722A
Surface-coated member and production method thereof
JP2014129562A
Compact fluid analysis device and manufacturing method
JP2020016659A
Surface-coated cutting tool with rigid coating layer exhibiting excellent chipping resistance
CN107614167A